Utilization of domestic wastewater for the growth of microalgae Chlorella sp. - Yuni Yolanda; Jenri Parlinggoman Hutasoit; Bagas Arya Nasution (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
This study investigates the potential of using domestic wastewater as a growth medium for Chlorella sp. and examines how it affects water quality over a period of 24 days. The experiment was conducted using a Completely Randomized Design (CRD) with a single factor: four levels of domestic wastewater concentration0%, 25%, 50%, and 75%each tested in three replicates.The results showed that the highest biomass production occurred on day 8, reaching 0.337 mg/L in the 75% wastewater treatment (TR3), while the lowest was observed in the control group (C) at 0.210 mg/L. Statistical analysis using ANOVA followed by the Tukey test confirmed that the differences between treatments were significant (p 0.05). Correlation analysis showed a strong positive correlation between biomass and dissolved oxygen (DO, 0.949) and temperature (0.626), indicating that optimal light intensity and nutrient availability promote photosynthesis and biomass growth. In contrast, phosphate was negatively correlated with temperature (-0.738), suggesting that higher temperatures accelerate phosphate uptake by Chlorella sp. The study concludes that cultivating Chlorella sp. using domestic wastewater presents a sustainable solution for both biomass production and wastewater treatment. The microalgae help remove excess nutrients like nitrogen and phosphorus, enhancing water quality. However, as the algae decompose, they can also contribute to higher biological oxygen demand (BOD). This dual role underscores the promising potential of microalgae in promoting ecological wastewater management while supporting sustainable biomass production.Keywords:BiomassChlorella sp.Photobioreactorwastewater